Arterial Stiffness as A Predictor of Future Cardiovascular Events: Methods of Measurement and Clinical Implications - Ardani Galih; Cholid Tri Tjahjono; Mohammad Saifur Rohman; Novi Kurniningsih (Universitas Brawijaya, 2023)
Arterial stiffness has recently emerged as strong predictor of cardiovascular events, including coronary heart disease. The cardio-ankle vascular index (CAVI) is a novel index that measures the overall stiffness of the artery all the way from the point where it branches off from the aorta to the ankle. CAVI's ability to provide accurate results regardless of the patient's blood pressure at the moment of measurement is without a doubt its most valuable characteristic. CAVI is related to many cardiovascular risk factors, including hypertension, diabetes mellitus, dyslipidemia, and smoking. It also increases with age and in many arteriosclerotic diseases, such as coronary artery disease, carotid arteriosclerosis, chronic kidney disease, and cerebrovascular disease. CAVI also increases in patients who have cerebrovascular disease. Controlling conditions such as diabetes mellitus and hypertension, in addition to quitting smoking, may also reduce the risk of CAVI. This indicates that CAVI is a physiological surrogate measure of atherosclerosis, and it also implies that it might be a signal of lifestyle change. Recent research has shown that CAVI and numerous functions of the left ventricle are linked to one another, which points to a linkage between the heart muscle and vascular function. This study discusses the fundamentals of CAVI as well as our present understanding of the measurement, with a particular emphasis on its functions and potential future use.